IMPROVING QUALITY OF LIFE FOR WOMEN WITH GENETIC-RELATED INFERTILITY - Salman, Dr. Alaa Abdulateef Mohammed; Khalaf, Dr. Alaa Kamel; Shareef, Dr. Rihab Majeed (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background: Infertility treatments significantly impact the quality of life for women, with poor psychological well-being often leading to higher rates of treatment discontinuation. Specific Background: In vitro fertilization (IVF) is a common intervention for genetically infertile women, yet its effects on quality of life remain underexplored, particularly using comprehensive tools like the Fertility Quality of Life Questionnaire (FERTIQOL). Knowledge Gap: Previous studies have not thoroughly assessed the impact of IVF on quality of life using FERTIQOL among genetically infertile women in specific geographic locations, such as Iraq. Aims: This study aims to evaluate the FERTIQOL among genetically infertile women undergoing IVF to determine its impact on their quality of life. Results: A total of 75 genetically infertile women, aged 20-45 years, were recruited from Baghdad hospitals between April 6, 2023, and October 10, 2024. The study found a 64% prevalence of primary infertility and a 36% prevalence of secondary infertility. Post-IVF complications occurred in 25.33% of cases, and pregnancy loss was reported in 32% of patients. Hormonal levels were recorded as follows: FSH 6.58 ± 0.05 IU/L, LH 6.52 ± 0.61 IU/L, estradiol 161.92 ± 6.18 pmol/L, and progesterone 0.89 ± 0.48 nmol/L. The FERTIQOL scores revealed a mean tolerability score of 76.55 ± 13.20, a treatment FertiQoL score of 67.91 ± 10.83, a relational score of 60.02 ± 8.74, and a Mind/Body score of 68.78 ± 16.59. Novelty: This study is among the first to assess the impact of IVF on quality of life in genetically infertile women using FERTIQOL in an Iraqi setting. Implications: The findings highlight the significant role of IVF in managing genetic infertility and its profound impact on patients' quality of life, underscoring the need for comprehensive support systems during treatment.